Efektivitas Metode Scramble untuk Meningkatkan Hasil Belajar Bahasa Arab Siswa Kelas X MA Takhassus Al-Qur’an Wonosobo - Silvi Nur Khasanah; Robingun Suyud El Syam; Ahmad Zuhdi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study was to analyze the effectiveness of the scramble method to improve the Arabic language learning outcomes of class X students of MA Takhassus AlQur'an Wonosobo. The article is a quantitative field research with an experimental approach. The research was conducted during the months of March to May 2025, involving 54 respondents as samples including control and experimental classes, taking data from observations, tests, interviews, and documentation. The results of the research showed that the application of the Scramble learning method had been carried out according to the learning implementation plan, using pre-tests and post-tests in the experimental class went well and received positive responses from students. There was an increase in students' Arabic language learning outcomes after applying the method in the experimental class, as evidenced by the results of the hypothesis with a gain test obtained a result of 0.624 (high category), the control class obtained a gain test result of 0.079 (moderate category). Real effectiveness can improve learning outcomes proven through t-test calculations obtained t_count results of 11.591 and t_table of 2.006 at a 5% error level and 2.673 at a 1% error level with dk = 27 + 27-2 = 52. This finding strengthens the Scramble method can be considered to improve student learning outcomes. Research recommends that in the teaching and learning process, it is possible to plan and consider various methods in learning so that students feel interested and not bored..